Models of diagnosing finance security of industrial enterprises - I. A. Sergeeva; S. Yu. Chunaev (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article grounds the necessity to develop a logit-model capable of showing specificity of Russian economy for diagnosing finance security of industrial enterprises in the Russian Federation. As a result of the research the authors designed two specialized models and put forward a classification of finance security for small and medium business. They showed the role of ensuring finance security of industrial enterprises and gave facts, which makes it possible to diagnose the start of finance threats. The article provides the analysis of Russian industrial enterprises dealing with machine and equipment manufacturing. The designed logit-models show finance processes of home industrial enterprises, which can cause finance insolvency. Testing was done on the basis of official open accounting of 173 Russian industrial enterprises. The authors produce evidence of their use for forecasting finance standing of Russian industrial enterprises. The research was done with the help of software IBM SPSS Statistics and it made it possible to give precise and trustworthy tests of the quality of logit-models. This research can be recommended for choosing efficient managerial solutions on ensuring finance security of industrial enterprises among diversified alternative concepts.